A Stigmasterol Containing n-hexane Fraction of Rauvolfia serpentina Methanolic Extract Shows Tissue-Specific Variation of Biocidal and Antioxidant Activities. Issue 1 (2nd January 2016) - Dey, Abhijit; Mukherjee, Souryadeep; De, Arijit; Pandey, Devendra Kumar
Abstract : Tissue-specific variation of stigmasterol in Rauvolfia serpentina and the corresponding biocidal and antioxidant activities of the methanol extract were measured using high-performance thin-layer chromatography. Stigmasterol had the highest concentration in the roots. The highest radical scavenging activity was seen in the root extract (60.94%) at 1 mg.mL −1 DPPH gradient; highest total phenolics content in 1 mg.mL −1 of the root extract was 67 μg of Gallic acid equivalent mg −1 d.w.; highest flavonoids present in the extract was 275 μg of Quercetin equivalent mg −1 d.w. The antibacterial activity was correlated to the amount of stigmasterol, total phenolics, total flavonoids, and antioxidants present in the plant parts.